HYPERREALITY IN SHARENTING: CHALLENGES OF BEING AN INDONESIAN PARENT TODAY - Arybowo, Yosepha; Widhiasti, Maria Regina (International Review of Humanities Studies, 2024)
The phenomenon of sharenting refers to the practice of parents, particularly mothers, sharing personal information in the form of text, photos, or videos about their child-rearing experiences and journey to parenthood on social media platforms. Social media, as a space of simulation, is considered to present an idealized version of parenting, showcasing perfect moments and achievements. This paper critically explores how the phenomenon of sharenting, especially by millennial mothers in Indonesia, contributes to the construction of family life representations that underlie parents' adaptation to idealized parenting standards on social media platforms. The paper samples sharenting content from several Instagram accounts considered as Indonesian “momfluencers”. Baudrillard's concept of hyperreality is employed to highlight the blurring of boundaries between reality and simulation in parenting practices, which can create unrealistic expectations for parents. By analyzing the intersection of sharenting and hyperreality as observed on the Instagram accounts of the sampled momfluencers, this paper discusses the implications for parents who may feel incapable or pressured to meet such parenting standards.